Tuning rules for unstable dead-time processes. (May 2021) - Sá Rodrigues, Rejane C.; Sombra, Andresa K.R.; Torrico, Bismark C.; Pereira, René D.O.; Forte, Marcus D.do N.; Filho, Magno P. de Almeida; Nogueira, Fabrício G.
Highlights: This paper proposes new tuning rules for unstable rst-order plus dead-time (UFOPDT) processes. The tuning method guarantee stability for delay uncertainty and is based on the maximum achievable robustness of the SFSP. Choosing the sampling time based on frequency domain analysis. Abstract: Despite many advances in the field of dead-time compensators (DTCs) for unstable first-order plus dead-time (UFOPDT) processes, the tuning, in general, is manually carried out. Therefore, this paper proposes simple tuning rules for a DTC intended to UFOPDT processes. The rules are based on the relative dead time, desired closed-loop time constant, and achievable robustness. Besides, as the practical implementation is always in the discrete-time domain, a method to choose the sampling period for UFOPDT processes is presented. Four simulation examples from the literature are used to show the advantages of the proposed method. In addition, an experiment with a propeller pendulum is performed to confirm such advantages in the control of a real unstable process with dead time.